Determinan Kualitas Laporan Keuangan Pemerintah Daerah : Investigasi Pemerintah Kota Yogyakarta : Determinants of the Quality of Regional Government Financial Reports: Investigation of the Yogyakarta City Government - Widodo, Sri; Afriany, Arista Natia; Sari, Monika Kurnia (Jurusan Akuntansi Politeknik Negeri Bandung, 2024)
In realizing good governance, regional governments need to continuously strive to increase transparency and accountability in regional financial management. The concrete manifestation of these efforts is the preparation of quality financial reports. However, in this modern era, various cases are still encountered, so this issue is still an interesting topic to review. This research is aimed at examining the determinants of the quality of financial reports in the Yogyakarta City government. This type of research is quantitative research with a research population covering 28 SKPDs in Yogyakarta City. The sampling technique uses a purposive sampling method with a sample size of 102 SKPD officials in Yogyakarta City. The data test tool uses SPSS version 21. According to the data test, government accounting standards and the use of information technology have a significant positive effect on the quality of local government financial reports, while source competency human resources have no effect on the quality of local government financial reports.